Penguatan Resiliensi Keluarga dan Ketangguhan Anak Usia Dini melalui Psikoedukasi Interaktif Berbasis Karakter Orang Tua Gigih di TK Negeri Assalam Cilegon - Mahsiani Mina Laili; Yuni Safira; Yunita Yuningsih (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2026)
This community service program aims to enhance family resilience awareness through interactive psychoeducational activities employing a character-strengthening approach for resilient parenting at TK Negeri Assalam Cilegon. The program involved 35 parents of kindergarten students as participants. Data were collected using pre-test and post-test questionnaires that measured four indicators: understanding of family resilience, parenting styles, parenting strategies, and strategies for strengthening the family's role based on the framework of the Ministry of Women's Empowerment and Child Protection (KemenPPPA). Scores were measured on a scale with a maximum value of 100%. The data were analyzed using the Normalized Gain (N-Gain) index. The results showed a substantial improvement in participants' knowledge, with the mean overall score increasing from 7.50% on the pre-test to 65.00% on the post-test. The greatest improvement was observed in the indicator measuring strategies for responding to children's failures, with an N-Gain score of 0.74 (high category). The overall mean N-Gain was 0.62, indicating a moderate level of improvement. These findings highlight the importance of integrating family resilience-based parenting programs into the school's ongoing educational agenda.